2021
DOI: 10.1155/2021/5571480
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Root Dentin Pretreatment on Micro-Push-Out Bond Strength of Fiber Posts to Root Canal Dentin: Cold Atmospheric Argon Plasma (CAAP) and Ethylenediaminetetraacetic Acid (EDTA)

Abstract: Purpose. Debonding from the root canal dentin is the most common failure mode of fiber posts. This study aimed to assess the effects of cold atmospheric argon plasma (CAAP) and ethylenediaminetetraacetic acid (EDTA) on micro-push-out bond strength of fiber posts to root canal dentin. Materials and Methods. Forty maxillary canine teeth were decoronated, underwent endodontic treatment, and were stored in an incubator for 7 days. After post space preparation, the teeth were randomly divided into four groups for d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
11
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 36 publications
1
11
1
Order By: Relevance
“…Prado et al (2016) concluded that argon plasma treatment increases the penetration of resin-based sealer into the dentin in the coronal third. The type of plasma, duration of use, and distance of the plasma jet nozzle from the plasma-prepared surface affect the bond strength of the resin.The present study shows that the CAP irradiation for 60 s has a significant effect on bond strength, unlike the results of Mahounak et al, which had a plasma irradiation parameter of 180 s. The distance between the plasma nozzle and the tooth was 1 cm in the present study and was 2 cm in the Mahounak study as longer distances can result in energetic gas molecules deviating around the instrument and escaping, thereby diminishing the effectiveness of the treatment(Sadeghi Mahounak et al, 2021). This difference appears to reduce the penetration of the CAP into the root canal and also explains the rationale for decreasing the time of plasma usage in this study.…”
contrasting
confidence: 88%
See 4 more Smart Citations
“…Prado et al (2016) concluded that argon plasma treatment increases the penetration of resin-based sealer into the dentin in the coronal third. The type of plasma, duration of use, and distance of the plasma jet nozzle from the plasma-prepared surface affect the bond strength of the resin.The present study shows that the CAP irradiation for 60 s has a significant effect on bond strength, unlike the results of Mahounak et al, which had a plasma irradiation parameter of 180 s. The distance between the plasma nozzle and the tooth was 1 cm in the present study and was 2 cm in the Mahounak study as longer distances can result in energetic gas molecules deviating around the instrument and escaping, thereby diminishing the effectiveness of the treatment(Sadeghi Mahounak et al, 2021). This difference appears to reduce the penetration of the CAP into the root canal and also explains the rationale for decreasing the time of plasma usage in this study.…”
contrasting
confidence: 88%
“…This study was conducted to evaluate the effect of root dentin surface pretreatment with CAP on improving the bond strength of fiber posts. In the present study, no surface treatments including etching or using sealants were performed because of the negative effect on bond strength (Lamichhane et al, 2014;Sadeghi Mahounak et al, 2021). Also, it has been stated that the weakest interface is between cement and root canal dentin, thus implying that surface treatment of fiber posts did not yield significant outcomes Abbreviations: AD, adhesive failure between dentin and cement (post is entirely covered with resin cement); AP, adhesive failure between cement and post (no cement remaining on the post); CD, cohesive failure in dentin; CP, cohesive failure in the post; EDTA, ethylenediaminetetraacetic acid; M1, mixed failure such that 0%-50% of the post surface was covered with cement; M2, mixed failure such that 50%-100% of the post surface was covered with cement.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations